Factors Influencing the Use of Code Crossing in EFL Classroom Interaction - Simpuruh, Indrayani; Syamsinar (JLE: Journal of Literate of English Education Study Program, 2023)
An appropriateness to use of code crossing in particular situation is needed. Specifically, in classroom interaction, when the lecturer and students should use code crossing. In fact, sometimes students use low code in classroom context. Hence, the researcher interested to analyze the factors influencing the use of code crossing used by the lecturer and students in classroom interaction. The research is qualitative research. The participant of the research is the student of Postgraduate program of UNM. The data was taken in classroom interaction use interview guide as the instrument of the research. The result of this research shows that the lecturer and students use both low and high code in classroom interaction. There are some reasons why they use low and high code in the classroom interaction. The data shows that there are seven factors that influence the lecturer and students to use code crossing. Those are; (1) power, (2) intimacy or non-intimacy, (3) hierarchical politeness, (4) social status, (5) social distance, (6) age and (7) formality